Kualitas Parameter Udara Ambien (Suhu, Pm10, SO2, dan Kebisingan) pada Lingkungan Perkantoran di Parepare - Dirman Sudarman; Nurul Hikmah; Amanda Salsa Nabila; Fahrul Syahisna Bayu; Fira Ramadhani; Hilda (Buletin Keslingmas, 2025)
Ambient air quality in office environments is one of the factors that influence worker comfort and health. Exposure to air pollutants such as sulfur dioxide (SO₂), particulate matter (PM₁₀), and noise levels can cause physiological and psychological disorders if they exceed established quality standards. This study aims to describe ambient air quality parameters including temperature, PM₁₀, SO₂, NO₂, CO, and noise in office environments in Parepare City. This study uses a descriptive approach with direct measurements in the field using standard air quality and noise instruments. The measurement data were analyzed by comparing them to the quality standards of the Governor of South Sulawesi Regulation Number 69 of 2010. The results showed that all air quality parameters such as SO₂ (262 µg/Nm³), NO₂ (0 µg/Nm³), CO (0 µg/Nm³), and PM₁₀ (28 µg/Nm³) were below the quality standards, so this condition indicates that office activities and traffic around the location have not contributed significantly to air pollution. The main scientific finding of this study is that only the noise parameter is slightly above the quality standards (65.30 dBA from the limit of 65 dBA), so it has the potential to cause discomfort and can be an environmental stressor for workers. The conclusion of this study confirms that ambient air quality is still relatively good, but noise control needs special attention as part of efforts to protect the health of the work environment.